Reproductive, maternal, newborn, and child health - Black, Robert E.; Laxminarayan, Ramanan; Temmerman, Marleen; Walker, Neff (Disease control priorities, 2016)
Health gains and financial risk protection afforded by treatment and prevention of diarrhea and pneumonia in ethiopia : an extended cost-effectiveness analysis / Stephane Verguet, Clint Pecenka, Kjell Arne Johansson, Solomon Tessea Memirie, Ingrid K. Friberg, Julia R. Driessen, and Dean T. Jamison